IMF Staff papers : Volume 7 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1960)
This paper explores the role of the IMF in promoting price stability. The IMF has one of its major objectives is to eliminate exchange restrictions that are due to balance of payments reasons. It carries on extensive annual consultations with its members toward that end; and, once the post-war transition is at an end, these members cannot impose exchange restrictions on current transactions without the approval of the Fund. This paper has consistently dealt with the IMF in its role of helping members to avoid inflation. Inflation is the subject of our meeting; and, in the post-war world as it has in fact developed, inflation, latent or realized, has been the perennial problem. Recessions have been short lived. Wherever a member is under pressure, either from external causes such as shrinkage in its foreign markets or from its own policies at home, the IMF stands ready to help it through its period of adjustment. Also with the notable strengthening of its resources that is now in the mill, it should prove to be an even more powerful bulwark against deflation. In such a world, those major countries that are maintaining the most stable and orderly price systems will set the standard to which others must repair.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet